Guide to developing quantitative tools for measuring gender norms in agrifood systems: IPSR Innovation Package and Scaling Readiness Report - Buono, Nicoletta; Kitalyi, Aichi; Mwakanyamale, Devis; Msita, Sarah (CGIAR Initiative on Gender Equality, 2024)
Working toward this objective, experts in social norms measurement from FHI360, an international development organization based in Washington, DC worked with IFPRI and IITA to co-develop a survey instrument to measure inequitable social and gender norms within cassava, fish, and chicken AgriFood-Systems (AFS). The instrument was developed through an iterative process including extensive stakeholder consultation and cognitive testing, and was piloted in Tanzania and Nigeria with actors operating in or supporting/ influencing the three AFS. The pilot data will be used to develop a counting based, multi-dimensional index measuring inequitable social and gender norms within the three target AFS. The index will be designed to be comparable across AFS, geographical regions, and between actor groups performing different AFS roles. The index can be used to inform the design of gender transformative approaches to address harmful social and gender norms in AFS.